The ratio of dietary diversity score versus energy density in relation to anthropometric and biochemical variables among patients with chronic kidney diseases - Rouhani, Mohammad Hossein; Mortazavi Najafabadi, Mojgan; Moeinzadeh, Firouzeh; Azadbakht, Leila (Progress in Nutrition, 2019)
Background: Some evidence showed that dietary diversity score (DDS), a diet quality index, was not always related to healthy outcomes. It seems that DDS to energy density ratio (DDS/ED) can overcome limitations of DDS.  The aim of current study was to assess the association between either dietary DDS or DDS/ED and nutrient intake, anthropometric and biochemical measures in subjects with chronic kidney disease (CKD). Methods: Two hundred seventy patients with CKD were randomly selected for this cross-sectional study. Dietary intakes were assessed using a 168-item semi quantitative food frequency questionnaire. Moreover, anthropometric indices, lipid profile, blood urea nitrogen (BUN) and high sensitivity C-reactive protein were measured. Results: Body mass index (BMI) had a significant negative trend across quartiles of DDS and DDS/ED. Also, a negative trend for waist circumference was observed across quartiles of DDS/ED. Although the trends of selenium (P